The adsorption of simple amines on platinum surfaces - Igoe, Anthony (Trinity College (Dublin, Ireland). School of Chemistry, 2001)
This thesis presents the results of an investigation of the adsorption of methylamine, dimethylamine, trimethylamine and ethylenediamine on Pt(111) and Pt(331). The chemical composition and geometric structure of the clean crystals were characterised by Auger electron spectroscopy, low energy electron diffraction, and X-ray photoelectron spectroscopy. Thermal desorption experiments have shown that, on heating the Pt(111) crystal, methylamine undergoes decomposition into H2, HCN and C2N2. A small amount of methylamine decomposes completely to leave carbon and nitrogen residues on the surface. The decomposition of methylamine on Pt(331) produces the same decomposition products as are produced on Pt(111). However, HCN desorption occurs at significantly lower temperatures. On both Pt(111) and Pt(331) a high temperature C2N2 peak is observed consistent with previous studies on methylamine, cyanogen and hydrogen cyanide adsorption on platinum.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin